Disparitas & Transformasi Struktural Antar Kabpuaten/Kota di Kalimantan - Maria Christina Yuli Pratiwi (Inovasi Pembangunan : Jurnal Kelitbangan, 2018)
The purpose of this paper to determine the uneven development across districts in Kalimantan and also to examines whether Kutnez hypothesis is applicable in Kalimantan. Klassen Typology, Williamson Index dan Entropy Theil Index, Structural Transformation, also Ratio Gini are employed in order to analysis the inequality of 56 districts in Kalimantan during 2010-2016. The result of study shows that: (1) the majority of regions on the island of Kalimantan belong to developed regions; (2) Kutnez hypothesis is applicable in Kalimantan; (3) regional inequality in Kalimantan shows an decline trend for the period of observation; (4) East Kalimantan province gives the largest contribution towards the inequality in Kalimantan; and (5) the highest structural transformation have been in Kutai Kartanegara District.